ANALISIS PENGARUH MODAL USAHA, TENAGA KERJA, TEKNOLOGI PEMASARAN TERHADAP PENDAPATAN UKM BATIK DI KABUPATEN SUMENEP - Rofiqi, Irfan; Susilo (Journal of Development Economic and Social Studies, 2023)
This research was conducted to analyze the effect of business capital, labor, marketing technology on the income of Batik SMEs in Pakandangan Village. This research uses business capital, labor and marketing technology as the independent variables, and income as the dependent variable. This study had a population of 291 while the sample used was 75 people. The data analysis method used is multiple linear regression analysis with SPSS software. The results showed that business capital and marketing technology had a significant positive effect on the income of Batik SMEs. This is in accordance with the theory used in research.